Usefulness of Automated cell counter in detection of malaria in a cancer set up –Our experience - Monica Jain; Surbhi Gupta; Jyotika Jain; R K Grover (Mediterranean Journal of Hematology and Infectious Diseases)
Malaria diagnosis presents a challenge to all laboratories. In malaria endemic areas there is a need for rapid, sensitive and cost effective method to effectively screen all samples especially when the workload is very high. Various hematology analyzers have been investigated for detection of malaria in the past. Here we present our experience of malaria detection in a cancer hospital where a large number of complete blood counts requests are received either before or during chemotherapy. Fever being a very common symptom in cancer patients causes a suspicion of malaria. This study was conducted to assess the usefulness of Hematology cell counter viz. WBC-DIFF & WBC/BASO scatter plots and the flaggings generated in malaria positive cases. The occurrence of pseudoeosinophilia as reported by previous studies was also assessed. The parasitic index was determined and its correlation with the abnormalities found on the hematology analyzers was also studied. Of the 80 patients who presented with fever 29 patients were positive for malaria and 10 cases were diagnosed incidentally by the findings on the cell counter and were confirmed by Giemsa stained blood smears. The instrument provides significantly valuable diagnostic parameters in detecting acute Pl.vivax malaria however it is not very useful for acute falciparum malaria infection. It is suggested that the laboratories using the Hematology analyzers should be aware of such specific parameters, even with the absence of a clinical request